JUVENTUDES E POLÍTICA DE ASSISTÊNCIA SOCIAL NO BRASIL PÓS-CONSTITUIÇÃO FEDERAL DE 1988: análise de programas e serviços - Maria D\u2019Alva Macedo Ferreira (Universidade Federal do Maranhão, 2020)
The article aims to discuss youth and Social Assistance, examining the guidelines of this policy with young people in the Brazilian reality after the 1988 Federal Constitution. The methodology used consisted of a bibliographic and documentary study, analyzing the aspects that permeate the recognition of youth as subjects of rights and the main programs implemented for young people since the 2000s in Brazil, based on a discussion about the guidelines put in place for social assistance services and for the management of the Unified Social Assistance System (SUAS), in order to examine whether these contribute to the visibility of interests, demands and needs, as well as to the assistance and participation of these social segments. The results show that, after the creation of the National Youth Secretariat and the approval of the Youth Statute, some actions were incorporated into the Brazilian public agenda based on programs for vulnerable young people, especially in preparation for work, which give continuity to a sectorialization perspective, considering that they do not constitute a more universalist dimension. Within the scope of the Social Assistance policy, this perspective is reiterated in the context of SUAS, given the fragility of the mechanisms of youth participation and the insufficiency / fragility of the services that are offered to these social segments.